Kualitas Serbuk Gergaji yang Difermentasi menggunakan Jamur Trichoderma viride - Lutojo Lutojo (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Amount of 18 bag sacks of sawdust have been used to know the influence of sawdust fermentation with Trichoderma viride on nutrition quality. Randomized complete block design of factorial 2x3 used as the experiment design in this research. First factor consist of 2 old level of ferment (10 and 20 day) and second factor consisting of 3 inoculums dose level (2, 3 and 4%). Variable observed are dry matter degradation, change of protein and fiber contains.